Menganalisis Strategi Pemasaran Pusat Oleh-oleh & Resto KAMOCI di Kabupaten Tegal - Saefudin Saefudin; Trenggono Trenggono; Shella Gherina Saptian; Haniek Listyorini; Dyan Triana Putra (Journal of Education, Humaniora and Social Sciences (JEHSS), 2024)
This article aims to explore and analyze the marketing strategies implemented by Pusat Oleh-oleh & Resto KAMOCI in Tegal Regency to address the increasingly competitive market. The focus of the research is on the challenges of maintaining product quality, responding to customer complaints, and leveraging information technology for competitive advantage. Utilizing theories of digital marketing strategies and customer satisfaction management, data were collected through in-depth interviews with managers and staff, as well as document analysis. The findings indicate that effective marketing strategies include the use of social media, collaboration with influencers, and the implementation of customer loyalty programs, all of which significantly contribute to brand awareness and customer retention. Additionally, the adoption of information technology, such as modern POS systems and mobile applications, plays a crucial role in enhancing operational efficiency and customer service. The conclusion of this study suggests that by strengthening marketing strategies and responding effectively to market feedback, Pusat Oleh-oleh & Resto KAMOCI can continue to compete and enhance customer satisfaction, achieving long-term success in a competitive market.